METHODS OF COMPILING AND SOLVING INTEGRAL PROBLEMS IN PHYSICS WITH LABOR EDUCATION - Mukhliboev, M.; Qurbanov, B.; Tuychiyev, A.; Boymatov, N. (International Journal of Psychosocial Rehabilitation, 2020)
This article aims to focus on the creation of a competition for problem-solving and problem solving that will enhance the attitude of general education students to integrating learning.